Perspectives on Collaborative Learning in ICT Mediated Classes as a Language Learning Booster - Buitrago García, Hilda Clarena (Rastros Rostros, 2021)
This article advocates for the implementation of collaborative learning in ict-mediated classes where a foreign language is taught. A documentary research analysis that involved reviewing academic articles was conducted to obtain a deeper understanding of this emerging instructional method. It offers a description of the advan-tages using different technologies has on language teaching and learning processes and how those technolo-gies can be used to provide collaborative learning environments. The distinctions between collaboration and cooperation are explained. The theoretical contributions that are central to the understanding of collaborative learning are outlined. Collaborative learning and its benefits are described. It has been found that collaborative learning enhances academic achievement through the development of a variety of social and critical thinking skills that require meaningful interactions and the willingness to embrace innovative ways to teach. Moreover, it was also found that using ict can increase the effectiveness of this teaching method since greater levels of motivation, creativity, and inclusion can be achieved.
Keywords: cooperative learning; Web 2.0; Learning; collaborative learning; ICT mediated instruction